"Great Men, " Law, and the Social Construction of Technology. Issue 3 (14th July 2017) - Swanson, Kara W.
Abstract : Is Alexander Graham Bell's fame owed to law and lawyers? Two recent histories argue that some popular tales of invention originated with lawyers and judges as part of patent litigation battles (Stathis Arapostathis and Graeme Gooday, Patently Contestable: Electrical Technologies and Inventor Identities on Trial in Britain [2013]; Christopher Beauchamp, Invented by Law: Alexander Graham Bell and the Patent That Changed America [2015]). Bringing law into the historical project of understanding the social construction of technology, the authors unsettle "great man" narratives of invention. A tale of a recent patent war is a case study in the persistence of such narratives, highlighting the uses of legal storytelling (Ronald K. Fierstein, A Triumph of Genius: Edwin Land, Polaroid, and the Kodak Patent War [2015]). Together, these works invite consideration of the cultural power possessed by invention origin stories, the role of narratives in law and history, and the judicial performance of truth finding in Anglo‐American law .